Soil Nutrients Drive Function and Composition of phoC-Harboring Bacterial Community in Acidic Soils of Southern China - Zheng, Man Man; Wang, Chao; Li, Wen Xing; Song, Wen Feng; Shen, Ren Fang (Frontiers in Microbiology, 2019)
Phosphorus (P) deficiency is an important factor that limits the agricultural production potential in acidic soils. The bacterial phoC gene encodes non-specific acid phosphatase (ACP), which participates in the mineralization of soil organic P and is therefore important for the improvement of soil P availability. However, the function and community population of phoC-harboring bacteria and their driving factors in acidic soil remain largely unknown. For this study, 51 soil samples and 207 plant samples were collected from four locations in the acidic soil region of southern China. Quantitative PCR and high-throughput sequencing were employed to analyze abundance and community composition of phoC-harboring bacteria. The results showed that soil P availability was the important nutrient element limiting the growth of both plants and soil bacteria. Soil ACP activity was clearly higher than alkaline phosphatase, indicating the important effect of phoC-harboring bacteria in acidic soils. ACP activity and phoC gene abundance showed a significant positive correlation, and both were closely related to soil available P, total carbon, and total nitrogen. The dominant genera of phoC-harboring bacteria involved Cupriavidus, Stenotrophomonas, and Xanthomonas. Compared to land-use pattern, sampling location, and soil parent material, soil property played a more important role in affecting phoC-harboring bacterial community structure, where N-related variables including soil NO3--N, NH4+-N, and C/N ratio appeared to be the main factor. These findings suggest that phoC-harboring bacteria should provide an important contribution to soil P availability in acidic soil, and its function and community composition were strongly associated with soil nutrients.